PENGARUH KEPEMIMPINAN DAN HUBUNGAN KERJA TERHADAP PENGEMBANGAN KARIR DAN KEPUASAN KERJA PEGAWAI DI KANTOR SEKRETARIAT PEMERINTAH DAERAH PROVINSI BALI - Matalia Matalia (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2012)
The purpose of this study was to know whether the leadership and working relationship has an influence to career development and whether career development, leadership and working relationship has an influence to job satisfaction. 255 employees in Secretariat Office of the Provincial Government of Bali were chosen with proportionate random sampling and data were collected by questionnaire. Analysis technique applies is SEM (Structural Equation Model). Based on the analysis, leadership and working relationship significantly influence employee career development. Career development and working relationships significantly influence employee satisfaction but leadership did not significantly influence employee satisfaction. This research implies that element of leadership and element of working relationships need to be increased in order to improve career development and career development needs to be improved in order to increase employee satisfaction through improved working relationship